Modeling of 14 nm gate length n-Type MOSFET - Faizah Z.A.N.; Ahmad I.; Ker P.J.; Roslan P.S.A.; Maheran A.H.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Dielectric materials; Fabrication; Field effect transistors; Gate dielectrics; Gates (transistor); Hafnium oxides; High-k dielectric; Metals; MOS devices; Nanoelectronics; Oxide semiconductors; Reconfigurable hardware; Threshold voltage; Transistors; ATHENA; ATLAS; High-k/metal gates; Metal gate transistors; MOS-FET; Short-channel effect; Virtual fabrication; Wafer fabrications; MOSFET devices